মধ্যবিত্তের বিকাশ ও ভোগবাদের উত্থান - রশীদ, মামুন (ঢাকা : আগামী প্রকাশনী, 2016)
Articles on various economic issues of contemporary Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Economics; Bangladesh -- Economic conditions -- 21st century .